Mental health problem recognition and stigma among emerging adults: Findings from the Voices for Well-Being Study (Project VOW) - Annie B. Fox; Jean-Phillipe Laurenceau; E. Carly Hill; Valerie A. Earnshaw (Social Psychiatry and Psychiatric Epidemiology, 2026)
Abstract Purpose Emerging adults experience the highest rates of mental health problems but the lowest rates of treatment engagement among U.S. adults. Stigma is a well-known barrier to care, undermining outcomes along the mental health treatment cascade from symptom recognition to treatment seeking. In the present study, we examine differences in experiences of stigma among emerging adults based on the presence, recognition, and/or diagnosis of mental health problems. Method The Voices for Well-Being (Project VOW) is a 12-wave longitudinal study of stigma and mental health in emerging adults (ages 18–21) recruited nationally via snowball and convenience sampling, surveyed quarterly for three years. Using baseline data, we classified participants into four groups: (1) no mental health problem history ( n = 608); (2) recognized and diagnosed ( n = 2566); (3) recognized and undiagnosed ( n = 1417) and (4) unrecognized mental health problem ( n = 91). We examined demographic profiles and compared groups across stigma mechanisms (stereotypes, prejudice, discrimination, perceived, anticipated, experienced, and internalized stigma) using ANCOVA models. Results The Project VOW Cohort is demographically diverse with a high mental health burden; 54.4% of participants reported a recognized and diagnosed mental health problem. Emerging adults with no or unrecognized mental health problems endorsed greater stereotypes, prejudice, and discrimination than those with recognized problems. Individuals with recognized and diagnosed conditions reported more experienced and internalized stigma than those with recognized but undiagnosed or unrecognized problems. Conclusion Findings highlight the critical role diagnoses play in shaping how people with mental illness are treated and view themselves, informing stigma intervention efforts for emerging adults.